PEMBELAJARAN KOOPERATIF DENGAN STRATEGI ”KARMIN ALJABAR” MENRAMPILKAN OPERASI HITUNG ALJABAR - Heru Wahyudi (saintifika, 2020)
The implementation of learning is expected to be active, innovative, creative, and fun without leaving the learning concepts. Calculating algebra is a very important learning and many students have difficulty. From the researcher's experience, learning algebra by utilizing the algebra domino card has an impact on students' interest in learning but learning outcomes don’t meet the completeness standards. Researchers strive for more interesting learning by giving deeper concepts in the learning process through cooperative learning with a contextual approach assisted by an Algebra Domino Card, which called "KARMIN Algebra". Based on the results for two cycles, it shows an increase, in cycle 1 obtained 72% of students reaching Minimum Standard Learning (MSL), while in cycle 2 obtained 84%. Meanwhile, the psychomotor and affective, shown that students are more skilled in calculating algebra. Referring to these results, the researchers suggest that this kind of learning can be used as an alternative to learning mathematics in schools by adjusting existing conditions.